Afterload reduction after non-invasive vagus nerve stimulation in acute heart failure - Nagai, Michiaki; Dote, Keigo; Kato, Masaya; Sasaki, Shota; Oda, Noboru; Förster, Carola Y. (Frontiers in Human Neuroscience, 2023)
Introduction While central blood pressure (BP) has been recognized as a major indicator of left ventricular (LV) afterload, the reduction of central pressure decreases LV afterload and may prevent heart failure (HF) decompensation. Non-invasive transcutaneous vagus nerve stimulation (tVNS) was shown to improve cardiac function in HF patients. In this study, the relationship between active tVNS and reduction of central BP was investigated in patients with acute HF (AHF). Methods The 22 patients hospitalized for AHF after initial stabilization (median 80 yrs, males 60%) were randomly assigned to active or sham group. For 1 h daily over 5 days, low-level transcutaneous electrical stimulation (LLTS) (20 Hz, 1 mA) was performed after attaching an ear clip to the tragus (active group) or the earlobe (sham control group). Before and after stimulation, central aortic systolic pressure (CASP), brachial systolic BP (SBP), diastolic BP (DBP) as well as heart rate (HR) were noninvasively measured. Results No significant differences in baseline characteristics were observed between the active and sham groups. In the active group, CASP, SBP, DBP, and HR each decreased significantly after stimulation (all p < 0.05), whereas in the sham group, CASP, SBP, DBP, and HR each increased significantly after stimulation (all p < 0.05). All the changes in CASP, SBP, DBP and HR before and after stimulation were also significantly different between active and sham groups (all p < 0.01). There were no device-related side effects. Conclusion In this study, the left tragus tVNS resulted in an acute afterload reduction in the elderly AHF patients. Non-invasive LLTS may be useful and safe for reducing afterload in AHF. Clinical trial registration ClinicalTrials.gov, identifier UMIN000044121.